Answer :
The formula for distance between two points is:
[tex]\sqrt{(x_{2} -x_{1})^{2} + (y_{2} -y_{1})^{2}}[/tex]
In this case:
[tex]x_{2} =-6\\x_{1} =-6\\y_{2} =-15\\y_{1} =2[/tex]
^^^Plug these numbers into the formula for distance like so...
[tex]\sqrt{(-6 -(-6))^{2} + (-15-2)^{2}}[/tex]
To solve this you must use the rules of PEMDAS (Parentheses, Exponent, Multiplication, Division, Addition, Subtraction) REMEMBER: IF A STEP IS NOT APPLICABLE TO THE EQUATION YOU MAY SKIP THAT STEP IN PEMDAS
First we have parentheses. Remember that when solving you must go from left to right
[tex]\sqrt{(-6 -(-6))^{2} + (-15-2)^{2}}[/tex]
-6 - (-6) = 0
[tex]\sqrt{(0)^{2} + (-15-2)^{2}}[/tex]
-15 - 2 = -17
[tex]\sqrt{(0)^{2} + (-17)^{2}}[/tex]
Next solve the exponent. Again, you must do this from left to right
[tex]\sqrt{(0)^{2} + (-17)^{2}}[/tex]
0² = 0
[tex]\sqrt{0 + (-17)^{2}}[/tex]
(-17)² = 289
[tex]\sqrt{(0 + 289)}[/tex]
Now for the addition
[tex]\sqrt{(0 + 289)}[/tex]
0 + 289 = 289
Now you must further simplify the square root
[tex]\sqrt{(289)}[/tex] = 17
The distance is 17 units
Hope this helped!
~Just a girl in love with Shawn Mendes